2023
DOI: 10.1021/acs.langmuir.2c03312
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Breakup of Oil–Particle Aggregates in Turbulent Environments for Projectile Penetration

Abstract: After an oil spill incident, the spilled oil slicks are observed to migrate to the shoreline area. Under the turbulent conditions, they break into small droplets and are suspended in the water column. The dispersed droplets are expected to interact with the suspended particles and form the oil–particle aggregates (OPAs), which significantly changes the transport of the oil. Instead of an earlier assumption that particles cover the oil surface, thus preventing further breakage or aggregation of OPAs, recent stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Consequently, we have adopted a conservative approach based on considering that oil particles are beached as soon as they reach a coastal cell. Whereas this approach ignores important mechanisms that govern the ultimate fate of the spill, such as the formation of oil particle aggregates 63 , 64 and oil bio-degradation 65 , the resulting compromise enables to avoid resorting to detailed resolution of the hydrodynamics in the near-shore region and consequently affords the efficiency needed to consider a wide array of potential release sources.…”
Section: Methods and Datamentioning
confidence: 99%
“…Consequently, we have adopted a conservative approach based on considering that oil particles are beached as soon as they reach a coastal cell. Whereas this approach ignores important mechanisms that govern the ultimate fate of the spill, such as the formation of oil particle aggregates 63 , 64 and oil bio-degradation 65 , the resulting compromise enables to avoid resorting to detailed resolution of the hydrodynamics in the near-shore region and consequently affords the efficiency needed to consider a wide array of potential release sources.…”
Section: Methods and Datamentioning
confidence: 99%
“…After oil spills, marine fragmentation waves break the oil slick into small droplets, and compared to the lower concentration of particles in the ocean, the abundant particles in the nearshore environment (especially in the surf zone and swash zone) are prone to form oil–particle aggregates (OPAs) with the oil droplets. The formation of OPAs further affects the vertical migration of oil droplets by reducing the adhesion property of the oil and making relatively stable OPAs more easily dispersed in water. ,,, It plays an important role in determining the transport and destination of oil spills. Furthermore, OPA formation also contributes to the biodegradation of oil spills. , Therefore, accurately capturing oil–particle–bacteria interactions is critical for predicting the transport and transformation of oil spills in the nearshore marine environments …”
Section: Introductionmentioning
confidence: 99%
“…Ji et al also found that due to the projectile mechanism, particle penetration of oil droplets reduces the droplet size and increases the contact area between oil and the hydrocarbon-degraders to promote oil spill biodegradation. Liu et al presented a numerical model to depict the kinetics of OPAs from oil transport to contact with sediments and finally to OPA settling and transport and provided insights into the biodegradation involving OPAs. However, the specific degradation effects and degradation characteristics of OPAs on marine oil spills are still unclear.…”
Section: Introductionmentioning
confidence: 99%